The interpersonal effects of emotion on rejection of severely unfair ultimatum proposal. Issue 1 (2nd October 2021) - Pietroni, Davide; Hughes Verdi, Sibylla; Giuliani, Felice; Rosa, Angelo; Missier, Fabio Del; Palumbo, Riccardo
Abstract : Purpose: The purpose of this study is to investigate how the emotion expressed by a fictitious proposer influences the responder's decision to accept or reject a severely unfair deal, represented by the splitting of a predetermined sum of money between the two players during an ultimatum game (UG). Rejection leads both parts to dissipate that sum. Critically the authors consider the situation in which both players have the best alternative to negotiation agreement (BATNA), which simulates a backup plan to rely on in case of no agreement. Design/methodology/approach: The participants played a UG and, to foster the ecological validity of the paradigm, the parts could both rely on a more or less generous BATNA. The critical manipulation was the emotion expressed by the proposer while their BATNA was either hidden (Exp. 1) or communicated (Exp. 2). Findings: The proposer's emotions influenced participants' own emotions, affected their social evaluations about the proposer, the desire for future interactions with the proposer and were used to infer the proposer's BATNA when it was unknown. In this latter case, proposers' emotions and in particular his/her happiness, decreased dramatically the participants' tendency to reject even severely unfair offers. Originality/value: Past research on UG has been predominantly aimed to investigate the effect of responders' emotions or the effects of responders' emotions on the proposer, devoting little attention to how the critical responder's acceptance/rejection decision might be affected by the proposer's emotion. Especially in the ecological situation where the parts have a BATNA in case of non-agreement.